Haulage trucks model with four electric separate wheel drives - Setlak, Rafal (Transport, 2005)
This article contains a course of work of the construction of a vehicle model that has four electrical motors built into each wheel. During the project two models of a vehicle were constructed (Figs 3, 5). A microprocessor based control system has also been designed and built. A vehicle is controlled by a steering unit (Fig. 8) which contains a steering wheel with a force feedback system, push buttons, an accelerator and a brake. The connection between a steering unit and a model is realized by interface RS‐485. The driving motors are dc motors with permanent magnets. Power supply consists of an acid battery located in the vehicle. The vehicle control system is divided into two parts. The first part is built into the vehicle (Fig. 7) and operates as a vehicle main control system and the second is built into a steering unit and operates as the main control steering system.First Published Online: 27 Oct 2010